The maintenance of conserved historic buildings in Malacca / Ahmad Najib Azizi - Azizi, Ahmad Najib (Faculty of Architecture, Planning and Surveying, 2014)
Conservation is one of the main process of the historic building and important knowledge.With respect to cultural heritage, conservation or art conservation focuses on protection and care of tangible and intangible of the building. Maintenance of the building is part of adding historic building life span. By adding know the flow process it can be well maintain as well for the future. Refer to the guidelines provide by the Jabatan Warisan Negara (JWN) support by local authority and other authority all the problem can be solve. This research are on historic building at malacca specific on certain building nominated by UNESCO as the heritage city in the world. 8 questionaire have been distributed to the 8 professional person with great experience they can share on conservation works and maintenance. The result on chapter four and chapter five analyzed as the conclusion of this research.